Implementasi Otonomi Daerah di Kabupaten Minahasa Selatan (Studi tentang Strategi Bidang Sumberdaya Manusia) - Onibala, Meiki M; Rumokoy, Donald A (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract. The purpose of this study to describe and analyze the implementation of regional autonomy, what factors are a barrier to implementation and strategies that need to be done to address them in South Minahasa regency. In this research, using qualitative methods, in which the primary data obtained through intensive observation and in-depth interviews to 15 informants. In addition, enriched with secondary data from documents, publications and other written references relevant to the implementation of regional autonomy. The results showed that basically the inherent authority to officials of local civil builder to manage resource issues in a very large apparatus ranging from the appointment process to denganpensiun. Staffing is not in accordance with the competence and expertise, but only based on the proximity to the decision-making authorities. Employee discipline and feel politicization employees is a major obstacle that inhibits autonomy. The strategy needs to be applied is the placement of officers in accordance with their competence and expertise, reinforce employee career paths, education and training of technical, functional and classes, and foster a culture of discipline. In addition, local governments need to improve the welfare of employees in order to have an impact on the quality of work and performance of government officials.Key words: Implementation of Regional Autonomy, Governance Strategy of Human Resources